Travessias das escolas do campo pela Pandemia da Covid-19: implicações nas metas do ODS-4 - Peres, Katiucia de Oliveira (2023)
On the last day of 2019, the world was alerted by the World Health Organization (WHO), of a disease that had just been detected in the People's Republic of China, and which was named SARS-CoV-2, later recognized as Covid -19. The disease soon turned into a pandemic and changed all plans for the year 2020, causing major inconvenience and deaths. In education, therefore, in March, the beginning of the regular school year, in-person classes were suspended, a situation that caused great difficulties, immeasurable consequences, requiring new pedagogical adaptations. Face-to-face teaching was replaced by distance learning, remotely, online, or otherwise due to technological problems. Thus, the objective of this study was to analyze the consequences of the Covid -19 Pandemic in the education of the Schools of the Field of the Nucleus de Education of Toledo, Paraná, based on the Sustainable Development Goals (ODS) and the interferences in the students' learning. Through the methodology of bibliographical research, information was collected and knowledge about the problem of the study was built through the scientific investigation of already published works. In this way, the study addressed the issue of the Sustainable Development Goals (SDGs) in the context of country Education in support of Family Agriculture, Family Sustainability in a Pandemic period, with a focus on a possible justification for an intellectual abandonment, and on the incidence of the pandemic in the intellectual abandonment of children and adolescents generating learning disorders. As a result, it was found that schools in Paraná were carrying out activities in the form of projects, related to the Sustainable Development Goals proposed by the UN, in particular SDG-4, which represents the area of education, with actions aimed at “Quality education”. With regard to family farming, projects of this magnitude could help in family development, contributing to the sustainability of families. It was also found a significant rate of children and adolescents developing child labor as a means of survival, due to the lack of public policies that would provide support, especially to the most vulnerable, affected by poverty due to existing social inequalities, informal and domestic work, causing damage to the physical and mental health in children and adolescents, with emphasis on the sexual exploitation of children and adolescents as forms of child labor. This violence found on the internet a place to expand its scope and structure its actions, where many fathers, mothers and family members profited at the expense of selling the bodies of the children they live with. Violence that affected the educational performance of children and adolescents, generating impacts that led to dropout and school dropout. In conclusion, we can believe that the Covid -19 pandemic has greatly harmed education in Paraná, especially in the most remote schools, in the case of rural schools and in Brazil in a general context, providing high levels of school dropout and even facts that come jeopardizing the achievement of SDG-4, which has as its principle a quality education for all.